The Effect of Axial Length Elongation on Corneal Biomechanical Property - Liu, Guihua; Rong, Hua; Zhang, Ping; Xue, Yu; Du, Bei; Wang, Biying; Hu, Jiamei; Chen, Zhi; Wei, Ruihua (Frontiers in Bioengineering and Biotechnology, 2021)
Background: To investigate the correlation between the corneal biomechanical parameter stress-strain index (SSI) and axial length (AL) in moderately elongated eye (MEE) and severely elongated eye (SEE). Methods: This study included 117 eyes from 117 participants. Among them, 59 (50.4%) had MEE (AL<26 mm) and 58 (49.6%) had SEE (AL≥26 mm). AL was measured using Lenstar LS-900, and central corneal thickness (CCT) and anterior chamber volume (ACV) were measured using Pentacam. SSI was measured via corneal visualisation Scheimpflug technology (Corvis ST). Kolmogorov-Smirnov test, Student’s t-test, and Pearson and partial correlation analyses were used for statistical analyses. Results: The mean (±SD) SSI was 1.08 ± 0.15 in the MEE group and 0.92 ± 0.13 in the SEE group (p < 0.01). SSI was positively correlated with age (MEE: r = 0.326, p < 0.05; SEE: r = 0.298, p < 0.05) in both groups; it was negatively correlated with AL (r = −0.476, p < 0.001) in the MEE group but not in the SEE group (p > 0.05). CCT was negatively correlated with AL (r = −0.289, p < 0.05) and ACV positively correlated with AL (r = 0.444, p < 0.001) in the MEE group. Neither CCT nor ACV was correlated with AL (p > 0.05) in the SEE group. Conclusion: Corneal biomechanical parameter SSI, which represents the stiffness of corneal tissue, was lower in the SEE group than in the MEE group. When analyzed separately, SSI was negatively correlated with AL in the MEE group, but not in the SEE group, which may provide insight into different ocular growth patterns between lower myopia and higher myopia.